2015
DOI: 10.1007/s11356-015-4801-3
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c adducts with PCB quinoid metabolites

Abstract: PCBs are a group of 209 individual congeners widely used as industrial chemicals. PCBs are found as by-products in dye and paint manufacture and are legacy, ubiquitous and persistent as human and environmental contaminants. PCBs with fewer chlorine atoms may be metabolized to hydroxy- and dihydroxy- metabolites and further oxidized to quinoid metabolites both in vitro and in vivo. Specifically, quinoid metabolites may form adducts on nucleophilic sites within cells. We hypothesized that the PCB-quinones covale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…The results show that the PCB3-pQ has the ability to form protein crosslinks. The protein crosslinks formation by PCB quinoid metabolites were also reported in previous research (Bender et al 2006, Qin et al 2013, Li et al 2015).…”
Section: Amount Of Pcb3 (Nmol) Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The results show that the PCB3-pQ has the ability to form protein crosslinks. The protein crosslinks formation by PCB quinoid metabolites were also reported in previous research (Bender et al 2006, Qin et al 2013, Li et al 2015).…”
Section: Amount Of Pcb3 (Nmol) Discussionsupporting
confidence: 79%
“…Protein adducts from polychlorinated biphenyls (PCBs) or PCB metabolites were identified by different research studies both in vitro and in vivo. PCB quinone metabolites have been found to form a covalent bond with human hydroxysteroid sulfotransferase hSULT2A1 (Qin et al 2013), with cytochrome c through lysine residues (Li et al 2015), and with glutathione and topoisomerase II (Srinivasan et al 2002), which caused a decrease of enzyme activity or dysfunction of proteins. Using radioactive compounds, PCB3 and PCB77 were found covalently bound to nuclear proteins in liver in vivo (Pereg et al 2001), and they were also shown to form hemoglobin adducts in vivo (Tampal et al 2003).…”
Section: )mentioning
confidence: 99%
“…The parameters and experimental conditions are given in Tab. 1. The values of a number of parameters such as feed concentration, carrier concentration, internal phase concentration, and treat ratio were varied during the extraction tests to observe their effects on AMX separation.…”
Section: Extractionmentioning
confidence: 99%
“…In recent years, much attention has been paid to research considering the reduction of water pollutants with significant studies on this issue [1][2][3]. The presence of these compounds in the environment leads to extensive microbial and chemical damages to the ecosystem exposed to wastewater [4].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, indomethacin and other NSAIDs are increasingly used in large amounts in human (and veterinary) medicine around the world, and despite sewage and wastewater treatment systems, many incompletely removed pharmaceuticals are released to the environment. Because of their harmful effects on humans and other organisms, pharmaceutical residues have attracted public attention [2,3] and various analytical methods have been used to monitor them in the environment.…”
Section: Introductionmentioning
confidence: 99%